TG/HDL-C ratio as a risk marker for metabolic syndrome and atherosclerosis in adolescents aged 15-18 years in Indonesia - Dwi Sarbini; Siti Zulaekah; Sudrajah Wirajati Kisnawaty; Farida Nur Isnaeni; Winda Wahyu Pratiwi; Maya Sukmawati; Sharla Apsarini (AcTion: Aceh Nutrition Journal, 2025)
Metabolic syndrome is characterized by high levels of triglycerides, blood glucose, and blood pressure, along with low high-density lipoprotein cholesterol (HDL-C) and central obesity. The TG/HDL-C ratio is a quick and cost-effective marker of dyslipidemia and insulin resistance, increasing the risk of atherosclerosis. However, most studies on TG/HDL-C ratio in Indonesia have been limited to adolescent populations with distinct metabolic profiles and health risks. This study aimed to assess the correlation between metabolic syndrome risk and TG/HDL-C ratio as a marker of atherosclerosis risk in adolescents. This cross-sectional study was conducted at Batik 1 Senior High School Surakarta from October 2023 to March 2024. A total of 65 adolescents were selected using simple random sampling. The observed data included body mass index (BMI), waist circumference, blood pressure, fasting blood glucose, triglycerides, HDL-C, metabolic syndrome risk, and atherosclerosis risk. Pearson and Spearman correlation tests were used for statistical analysis. The results showed A significant correlation was observed between TG/HDL-C ratio and atherosclerosis risk (p= 0,000), waist circumference (p= 0,009), systolic blood pressure (p= 0,001), and diastolic blood pressure (p= 0,000). However, no significant correlation was found between fasting blood glucose level (p= 0,905) and BAZ (p= 0,405). In conclusion, TG/HDL-C ratio can serve as a valuable indicator for assessing metabolic syndrome risk in adolescents, allowing for early intervention to reduce the risk of atherosclerosis.